The mutualism of Melissotarsus ants and armoured scale insects in Africa and Magadascar: distribution, host plants and biology - Ben-Dov, Y.; Fisher, B.L. (ENTOMOLOGIA HELLENICA, 2010)
Species of the ant genus Melissotarsus Emery are widespread in the Afrotropical region (three species, namely M. beccarii Emery, M. emeryi Forel and M. weissi Santschi) and in the Madagascar region (one species, namely M. insularis Santschi). The ants of all these species tunnel their galleries in live wood of various dicotyledonous trees, close to the bark surface. The ants maintain within these galleries populations of different species of armoured scale insects. A review is presented on the geographical distribution of mutualism, of the Melissotarsus species, the associated 10 species of armoured scale insects, and the host plants on which the mutualism takes place. The ecology of the mutualism is discussed also, together with suggestions on the benefits that the partners gain from the associations.